Peran Pemerintah dalam Ketahanan Pangan Nasional: Tinjauan Literatur Sistematis dan Analisis Bibliometrik - Nurhayati; Winda Roselina Effendi; Ramon Zamora; Utami Yerikania (Jurnal Bina Praja, 2026)
This study examines the role of government in strengthening national food security through a hybrid approach combining a systematic literature review (SLR) and bibliometric analysis. Literature data were collected from the Scopus database using the query "government role AND food security," yielding 22 articles for qualitative synthesis. The findings identify four key governance dimensions: local government initiatives, national government support, agricultural policy, and intersectoral collaboration. Effective food security governance requires coordinated action across levels of government, supported by clear legislation, adequate funding, and partnerships with civil society and the private sector. Agricultural policies promoting smallholder farmer groups, technology access, and sustainable practices further strengthen food availability and household-level resilience. Bibliometric analysis reveals dominant research clusters around policymaking, climate change, food insecurity, and governance, reflecting the multidimensional nature of food security challenges. However, several implementation barriers persist, including weak intergovernmental coordination, limited rural infrastructure, low technology adoption among smallholder farmers, and insufficient adaptive capacity in the face of climate change. This study highlights the need for integrated, adaptive, and evidence-based governance frameworks to achieve sustainable and inclusive food security outcomes.